Synthesis of polystyrene living nanoparticles (LNPs) in water via nano-confined free radical polymerization. Issue 46 (6th November 2020) - Chang, Wei-Ting; Sie, Jyun-Hao; Tsai, Ya-Wen; Chen, Yi-Wei; Peng, Chi-How; Wang, Xiaosong; Wang, Chien-Lung
Abstract : Nano-confined free radical polymerization of styrene within the hydrophobic interior of a unimolecular micelle in water was developed to produce living nanoparticles (LNPs) that contain living mono-disperse polystyrenes for further chain extension. Abstract : Living nanoparticles (LNPs), analogs of living polymers, are particles that contain active species for further polymerization. We created these novel nanoparticles via free radical polymerization of styrene encapsulated within the hydrophobic interior of a unimolecular micelle (UM) in water. The resultant particles contain mono-disperse polystyrenes with active free radicals. The livingness of the particles was verified by the reaction with radical scavengers and their capability to initiate further polymerization of either water-insoluble or water-soluble monomers. This creation of LNPs is unprecedented and opens a new technique for polymer synthesis using particle initiators.